2022
DOI: 10.1177/03009858221092015
|View full text |Cite
|
Sign up to set email alerts
|

Animal models for studying COVID-19, prevention, and therapy: Pathology and disease phenotypes

Abstract: Translational models have played an important role in the rapid development of safe and effective vaccines and therapeutic agents for the ongoing coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Animal models recapitulating the clinical and underlying pathological manifestations of COVID-19 have been vital for identification and rational design of safe and effective vaccines and therapies. This manuscript provides an overview of commonly used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 103 publications
0
9
0
Order By: Relevance
“…Due to their low cost, small size and rapid breeding, mouse models (transgenic mouse expressing hACE2, hACE2-transduced mouse, mouse adapted SARS-CoV-2 strain and hACE2 humanized mouse) and hamster models have been used with some limitations, such as lack of severity of the respiratory symptoms. The cynomolgus macaque model was reported to be suitable for studying the pathology and immune responses of the SARS-CoV-2 infection due to the close genetic similarity of cynomolgus macaques to humans; however, their limited availability, the ethical concerns, and the high cost related to the need for complex husbandry restrict their frequent usage in preclinical COVID-19 investigations [ 39 , 40 , 41 , 42 , 43 ]. It was also reported that liver metabolism in cynomolgus monkeys shows strong resemblance to that in humans, including the CYP expressions and drug uptake of hepatocytes, thereby allowing better prediction of human in vivo intrinsic hepatic clearance [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to their low cost, small size and rapid breeding, mouse models (transgenic mouse expressing hACE2, hACE2-transduced mouse, mouse adapted SARS-CoV-2 strain and hACE2 humanized mouse) and hamster models have been used with some limitations, such as lack of severity of the respiratory symptoms. The cynomolgus macaque model was reported to be suitable for studying the pathology and immune responses of the SARS-CoV-2 infection due to the close genetic similarity of cynomolgus macaques to humans; however, their limited availability, the ethical concerns, and the high cost related to the need for complex husbandry restrict their frequent usage in preclinical COVID-19 investigations [ 39 , 40 , 41 , 42 , 43 ]. It was also reported that liver metabolism in cynomolgus monkeys shows strong resemblance to that in humans, including the CYP expressions and drug uptake of hepatocytes, thereby allowing better prediction of human in vivo intrinsic hepatic clearance [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 involves complex host-pathogen interactions; therefore, it is necessary to develop animal models that can provide measurable readouts for potential interventions ( Johansen et al, 2020 ; Muñoz-Fontela et al, 2020 ; Villano, 2021 ; Choudhary et al, 2022 ). To rapidly evaluate these potential medical countermeasures, such as therapeutic drugs and preventive vaccines, animal models that were susceptible to SARS-CoV-2 infection are invaluable ( Zeiss et al, 2021 ; Choudhary et al, 2022 ; Fan et al, 2022 ; Golden et al, 2022 ; Qi and Qin, 2022 ; Rizvi et al, 2022 ; Zhao et al, 2022 ). However, wild-type mice do not support SARS-CoV-2 replication due to the incompatibility of mouse ACE2 with the spike protein of SARS-CoV-2 ( Yang et al, 2007 ; Golden et al, 2020 ; Oladunni et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…31 Comparisons of lung pathology in mice and other species are discussed. 9 The hACE2-transgenic mice tend to develop the most diffuse and severe lung lesions, sometimes leading to marked clinical disease and death, which is not found in other animal models. In contrast, wild-type mice are resistant to infection generally due to virus-receptor incompatibility.…”
mentioning
confidence: 98%
“…The various animal models and their applications for study of SARS-CoV-2 infection is reviewed as an introduction to the issue. 9 Working with these viruses requires biological safety level-3 (BSL-3) animal and laboratory containment, which presents some challenges, and involves defined safety standards and biosafety protocols for necropsy and tissue handling and storage. 4 The histopathology of SARS-CoV-2 infection in mice, hamsters, NHPs, ferrets, and cats has been described by many authors, but there is no uniform histopathology nomenclature for the lung and upper respiratory tract lesions.…”
mentioning
confidence: 99%
See 1 more Smart Citation